(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
At present, we are participants and observers of the formation of a new world order, where the position of Asian states is being strengthened in the world political and economic arena. This is primarily due to the continent of Eurasia. As a result of the ongoing reforms, China has become the economic locomotive of the world. In the foreign policy of this state, the Central Asian region plays an important economic and geopolitical role. Since for the development of the economy, China needs natural resources available on the territory of the states of Central Asia. On the other hand, there are also interests of such leading actors of the world as the USA, the Russian Federation. Despite the fact that China has established relations with the region since ancient times, at present, Beijing has formed specific relations with each state of Central Asia. In this respect, Beijing’s Belt and Road Initiative is of great importance.